Slaughterhouse Wastewater Treatment: A Review on Recycling and Reuse Possibilities - Maximilian Philipp (MDPI AG, 2021)
Slaughterhouses produce a large amount of wastewater, therefore, with respect to the increasing water scarcity, slaughterhouse wastewater (SWW) recycling seems to be a desirable goal. The emerging challenges and opportunities for recycling and reuse have been examined here. The selection of a suitable process for SWW recycling is dependent on the characteristics of the wastewater, the available technology, and the legal requirements. SWW recycling is not operated at a large scale up to date, due to local legal sanitary requirements as well as challenges in technical implementation. Since SWW recycling with single-stage technologies is unlikely, combined processes are examined and evaluated within the scope of this publication. The process combination of dissolved air flotation (DAF) followed by membrane bioreactor (MBR) and, finally, reverse osmosis (RO) as a polishing step seems to be particularly promising. In this way, wastewater treatment for process water reuse could be achieved in theory, as well as in comparable laboratory experiments. Furthermore, it was calculated via the methane production potential that the entire energy demand of wastewater treatment could be covered if the organic fraction of the wastewater was used for biogas production.